The Effect of Intellectual, Emotional, and Spiritual Intelligence on the Economic Learning Achievement of SMA Negeri 1 Soppeng - Yahya, Muh.; Radjab, Mulyadi; Satriyani, Satriyani (FKIP-Universitas Riau, 2020)
This study aimed to examine emotional intelligence significantly influence students’ economic learning achievement and stimulatingly examine the effect of intellectual, emotional, and spiritual intelligence on student’s economic learning achievement in SMA Negeri 1 Soppeng. Afterward, this study included as descriptive quantitative study. Population the study was all students of SMA Negeri 1 Soppeng which is 955 students. 90 students were chosen as sample, using simple random sampling technique. Data collection techniques used questionnaire and documentation. Data analysis used descriptive analysis, analysis test requirements, and data analysis used SPSS 21 program. Result of this study showed that intellectual intelligence variable significantly influence on economic learning achievement of students; emotional intelligence variable significantly influences the economic learning achievement of students; spiritual intelligence variable significantly effects the economic learning achievement of students; and There was significant variables of intellectual, emotional, and spiritual intelligence on the economic learning achievement. Determination coefficient of X1, X2, and X3 to Y (r2Y.123) was 0,153 which showed that intellectual, emotional, spiritual intelligence factors have contribution to influence economic learning achievement of students in SMA Negeri 1 Soppeng that was 15,3%, while 84,7% was influenced by another variable that was not analyzed.